2007
DOI: 10.1021/bc070020r
|View full text |Cite
|
Sign up to set email alerts
|

Surface Engineering of Quantum Dots for In Vivo Vascular Imaging

Abstract: Quantum dot-antibody bioconjugates (QD-mAb) were synthesized incorporating PEG cross-linkers and Fc-shielding mAb fragments to increase in vivo circulation times and targeting efficiency. Microscopy of endothelial cell cultures incubated with QD-mAb directed against cell adhesion molecules (CAMs), when shielded to reduce Fc-mediated interactions, were more specific for their molecular targets. In vitro flow cytometry indicated that surface engineered QD-mAb labeled leukocyte subsets with minimal Fc-mediated bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
76
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(77 citation statements)
references
References 43 publications
1
76
0
Order By: Relevance
“…molarity was about 0.227 nM to 227 nM). According to previous reports, the concentration which we tested in our following experiments is similar to the doses that have actually used in in vivo bioimaging (up to hundreds of nanomole) (Ballou et al 2007;Ballou et al 2004;Cai et al 2006;Gao et al 2004;Jayagopal et al 2007;Larson et al 2003;Tada et al 2007) or tested in other in vitro toxicological studies (up to hundreds of nanomole or μg/mL) 20 (Chang et al 2009;Chen et al 2010;Choi et al 2007;Lovric et al 2005;Su et al 2009;Su et al 2010;Tang et al 2008;Wu et al 2010). Then, our cell viability assays (Fig.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…molarity was about 0.227 nM to 227 nM). According to previous reports, the concentration which we tested in our following experiments is similar to the doses that have actually used in in vivo bioimaging (up to hundreds of nanomole) (Ballou et al 2007;Ballou et al 2004;Cai et al 2006;Gao et al 2004;Jayagopal et al 2007;Larson et al 2003;Tada et al 2007) or tested in other in vitro toxicological studies (up to hundreds of nanomole or μg/mL) 20 (Chang et al 2009;Chen et al 2010;Choi et al 2007;Lovric et al 2005;Su et al 2009;Su et al 2010;Tang et al 2008;Wu et al 2010). Then, our cell viability assays (Fig.…”
Section: Discussionmentioning
confidence: 92%
“…Lately, QDs were reported to label dermal, adipose, tumor and retinal vasculature (Cai et al 2006;Jayagopal et al 2007;Larson et al 2003). These angiographic techniques provide noninvasive optical access to the vasculature and continuous monitoring of vascular functions.…”
Section: Introductionmentioning
confidence: 99%
“…Antibody fragments possessing free thiol groups have been bound to free amino groups of quantum dots by means of a heterobifunctional crosslinker (Jayagopal et al 2007), and biotinylated antibodies to streptavidin-modified quantum dots (Dahan et al 2003). More protocols and a comparison of the different approaches have been carried out recently (Xing et al 2007).…”
Section: (Iii) Peptides Proteins Enzymes and Antibodiesmentioning
confidence: 99%
“…As to chemical functional groups, there are a number of colorimetric assays reported that allow for the quantification of amine groups, thiols and others (Ballou et al 2004;Jayagopal et al 2007). Possibly, a chromophore released by the reaction with the target analyte (Zhao et al 2002a;Maus et al 2009) has to be separated from the nanoparticles because of overlapping absorption spectra.…”
Section: (E) Characterizationmentioning
confidence: 99%
“…22,25 Nevertheless, many researchers have observed various nonspecific imaging and passive targeting properties of QDs, namely, the behavior of the QDs but not the functional groups. 26,27 Therefore, to better understand and predict the efficacy and side effects of QDs in vivo, some key questions need to be addressed: Where are these nanocrystals deposited within the tissue and cell?…”
Section: Introductionmentioning
confidence: 99%